Collective Engagement and Social Identity of the "Taruno Suryo" Reog Community to Improve Spiritual Well-Being - Alfiana Yuniar Rahmawati; Asrifia Ridwan (Insaniyat: Journal of Islam and Humanities, 2026)
This study examines the concept of collective engagement and social identity in the context of the "Taruno Suryo" Reog Art Community as a strategic approach to improving the community's spiritual well-being. This descriptive qualitative research, using a case study approach, applies purposive sampling to select key subjects from the community. Data were collected through in-depth interviews, participant observation, and documentation. Furthermore, the data were analyzed and interpreted using symbolic interactionism theory and social identity theory to explore how symbolic interaction in Reog art practices can strengthen collective bonds and social identity, thereby supporting shared spiritual well-being. The results of the study indicate that the concept of collective engagement, manifested through members' active involvement in every Reog art activity, can serve as a basis for interaction that, in turn, gives rise to social identity as a pillar for strengthening the solidarity of cultural inheritors. The process of internalizing cultural values and religiosity serves as a forum for fostering spiritual well-being. The integration of these concepts can make the "Taruno Suryo" Reog art community one of the art media capable of fostering the spiritual well-being of community members by internalizing the cultural values ​​of Reog Ponorogo in every art activity.